Pengaruh Keselamatan dan Keseahtan Kerja terhadap Produktivitas Karyawan Pabrik di PT Mitra Aneka Rezeki - Dewi Pratiwi, Amriyani; Zunaidah; M. Ichsan Hadjri; Santati, Parama (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted aiming to determine the effect of Occupational Safety and Health on the Productivity of Factory Employees at PT Mitra Aneka Rezeki. The population in this study were all employees at PT Mitra Aneka Rezeki, totaling 90 people and taking samples using census sampling. Methods of data collection using interviews and questionnaires. The analysis technique used is simple regression analysis. Based on the results of the analysis, it was concluded that occupational safety and health had a positive and significant effect on employee productivity at PT Mitra Aneka Rezeki. We hope that PT Mitra Aneka Rezeki can continue to evaluate and improve occupational safety and health for employees through providing sufficient and proper work facilities and equipment and keeping employees safe. so that employees can increase work productivity that is satisfactory for PT Mitra Aneka Rezeki.